Blood foam [large type] : a Lewis Cole mystery - DuBois, Brendan (DuBois, Brendan. Lewis Cole mystery., 2015)
Lewis Cole -- retired Department of Defense analyst and magazine columnist -- returns to his fire-damaged home on Tyler Beach to recover from a bullet wound and repair his nearly two hundred-year-old home before a hurricane. Then former lover Paula Quinn comes to him with an urgent request for help: her fiancé has gone missing.